Low‐intensity Pulsed Ultrasound Enhances Bone Repair in a Rabbit Model of Steroid‐associated Osteonecrosis. Issue 5 (May 2015) - Zhu, Hanxiao; Cai, Xunzi; Lin, Tiao; Shi, Zhongli; Yan, Shigui
Abstract: Background: Steroids are a leading cause of femoral head osteonecrosis. Currently there are no medications available to prevent and/or treat steroid‐associated osteonecrosis. Low‐intensity pulsed ultrasound (LIPUS) was approved by the FDA for treating delayed union of bone fractures. Some studies have reported that LIPUS can enhance bone formation and local blood flow in an animal model of fracture healing. However, whether the effect of osteogenesis and neovascularization by LIPUS can enhance the repair progress in steroid‐associated osteonecrosis is unknown. Questions/purposes: We hypothesized that LIPUS may facilitate osteogenesis and neovascularization in the reparative processes of steroid‐associated osteonecrosis. Using a rabbit animal model, we asked whether LIPUS affects (1) bone strength and trabecular architecture; (2) blood vessel number and diameter; and (3) BMP‐2 and VEGF expression. Methods: Bilateral femoral head necrosis was induced by lipopolysaccharide and methylprednisolone in 24 rabbits. The left femoral heads of rabbits received LIPUS therapy (200 mW/cm 2 ) for 20 minutes daily and were classified as the LIPUS group. The right femoral heads of the same rabbits did not receive therapy and were classified as the control group. All rabbits were euthanized 12 weeks after LIPUS therapy. Micro‐CT, biomechanical testing, histologic evaluation, immunohistochemistry, quantitative real‐time PCR, and Western blot were used for examination of the effects of LIPUS. Results: Twelve weeks after LIPUS treatment, the loading strength in the control group was 355 ± 38 N (95% CI, 315‐394 N), which was lower (p = 0.028) than that in the LIPUS group (441 ± 78 N; 95% CI, 359‐524 N). The bone tissue volume density (bone volume/total volume) in the LIPUS group (49.29% ± 12.37%; 95 % CI, 36.31%‐62.27%) was higher (p = 0.022) than that in the control group (37.93% ± 8.37%; 95 % CI, 29.15%‐46.72%). The percentage of empty osteocyte lacunae in the LIPUS group (17% ± 4%; 95% CI, 15%‐20%) was lower (p = 0.002) than that in the control group (26% ± 9%; 95% CI, 21%‐32%). The mineral apposition rate (μm/day) in the LIPUS group (2.3 ± 0.8 μm/day; 95% CI, 1.8 2.8 μm/day) was higher (p = 0.001) than that in the control group (1.6 ± 0.3 μm/day; 95% CL, 1.4‐1.8 μm/day). The number of blood vessels in the LIPUS group (7.8 ± 3.6/mm 2 ; 95% CI, 5.5‐10.1 mm 2 ) was greater (p = 0.025) than the number in the control group (5.7 ± 2.6/mm 2 ; 95% CI, 4.0‐7.3 mm 2 ). Messenger RNA (mRNA) and protein expression of BMP‐2 in the LIPUS group (75 ± 7, 95% CI, 70‐79; and 30 ± 3, 95% CI, 28‐31) were higher (both p < 0.001) than those in the control groups (46 ± 5, 95% CI, 43‐49; and 15 ± 2, 95% CI, 14‐16). However, there were no differences (p = 0.114 and 0.124) in mRNA and protein expression of vascular endothelial growth factor between the control (26 ± 3, 95% CI, 24‐28; and 22 ± 6, 95% CI, 18‐26) and LIPUS groups (28 ± 2, 95% CI, 26‐29; and 23 ± 6, 95% CI, 19‐27). Conclusions: The results of this study indicate that LIPUS promotes osteogenesis and neovascularization, thus promoting bone repair in this steroid‐associated osteonecrosis model. Clinical Relevance: LIPUS may be a promising modality for the treatment of early‐stage steroid‐associated osteonecrosis. Further research, including clinical trials to determine whether LIPUS has a therapeutic effect on patients with early‐onset steroid‐associated osteonecrosis may be warranted.